2019
DOI: 10.1097/md.0000000000017996
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the frequent exacerbators with chronic bronchitis phenotype and the asthma-chronic obstructive pulmonary disease overlap syndrome phenotype in chronic obstructive pulmonary disease patients

Abstract: To investigate the difference of clinical characteristics between chronic obstructive pulmonary disease (COPD) patients with the frequent exacerbators with chronic bronchitis (FE-CB) phenotype and those with the asthma-COPD overlap syndrome (ACO) phenotype. We searched CNKI, Wan Fang, Chongqing VIP, China Biology Medicine disc, PubMed, Cochrane Library, and EMBASE databases for studies published as of April 30, 2019. All studies that investigated COPD patients with the FE-CB and ACO phenotypes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The language was restricted to English or Chinese. Referring to our previous research [5], the research was obtained using the following keywords or combinations: "Chronic Obstructive Pulmonary Disease" or "COPD"; merging "Non-exacerbators" or "Nonexacerbators" or "nonexacerbator" or "non-frequent exacerbators with chronic bronchitis or emphysema" or "non-exacerbator phenotype with either chronic bronchitis or emphysema" or "NE" or "NONEX" or "NE-CB/E" or "NON-AE", merging "frequent exacerbator(s) with chronic bronchitis" or "exacerbator(s) with chronic bronchitis" or "exacerbator phenotype with chronic bronchitis" or "FE-CB". In order to avoid omissions, the references of relevant reviews and meta-analyses were manually screened.…”
Section: Search Strategymentioning
confidence: 94%
See 2 more Smart Citations
“…The language was restricted to English or Chinese. Referring to our previous research [5], the research was obtained using the following keywords or combinations: "Chronic Obstructive Pulmonary Disease" or "COPD"; merging "Non-exacerbators" or "Nonexacerbators" or "nonexacerbator" or "non-frequent exacerbators with chronic bronchitis or emphysema" or "non-exacerbator phenotype with either chronic bronchitis or emphysema" or "NE" or "NONEX" or "NE-CB/E" or "NON-AE", merging "frequent exacerbator(s) with chronic bronchitis" or "exacerbator(s) with chronic bronchitis" or "exacerbator phenotype with chronic bronchitis" or "FE-CB". In order to avoid omissions, the references of relevant reviews and meta-analyses were manually screened.…”
Section: Search Strategymentioning
confidence: 94%
“…GesEPOC identifies four phenotypes: non-exacerbator (NE), asthma-COPD overlap (ACO), exacerbator with emphysema (FE-E), and frequent exacerbator with chronic bronchitis (FE-CB) [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had explored the characteristic of BMI in COPD patients with the emphysema phenotype and the bronchitis phenotype. Studies had shown that the emphysema phenotype had a lower BMI than those with the bronchitis phenotype [5]. However, the characteristic of BMI in the FE-CB and NE phenotypes is still controversial.…”
Section: P<0001 I 2 =38%mentioning
confidence: 99%
“…The language was restricted to English or Chinese. Referring to our previous research [5] , the research was obtained using the following keywords or combinations: "Chronic Obstructive Pulmonary Disease" or "COPD";…”
Section: Search Strategymentioning
confidence: 99%